2013
DOI: 10.1177/002795011322500106
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Bank Lending to UK SMEs in the wake of the crisis

Abstract: The availability of bank finance to small and medium sized enterprises (SMEs) is important to allow SMEs to start up and finance investment for growth. To assess changes in such availability over 2001–12, we used data from a series of surveys that provide detailed information on the characteristics of a sample of UK SMEs, their owners and experiences of obtaining finance. Using econometric models, which included controls for SME characteristics and risk factors, indicators of changes in the provision of bank l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 9 publications
5
22
0
Order By: Relevance
“…(Note their paper goes to BSD2010, which in our terms refers to 2009.) consistent with a reduction in funds for investment, for example through constraints on credit as identified in Armstrong et al (2013) than an exogenous shock to demand.…”
Section: Net Job Creationmentioning
confidence: 64%
See 1 more Smart Citation
“…(Note their paper goes to BSD2010, which in our terms refers to 2009.) consistent with a reduction in funds for investment, for example through constraints on credit as identified in Armstrong et al (2013) than an exogenous shock to demand.…”
Section: Net Job Creationmentioning
confidence: 64%
“…By contrast 2010 and 2011 are years of unusually low churn, continuing the low gross job creation of downturn period. This could reflect ongoing reduced credit through restrictions on the availability of SME bank finance to 2012 as identified in Armstrong et al (2013). The slowdown in net creation (middle line) in 2008 is accounted for by the fall in entry (first block above zero).…”
Section: Net Job Creationmentioning
confidence: 99%
“…In a detailed investigation of the SME Finance Monitor, Armstrong et al (2013), found that rejection rates for both overdrafts and term loans were significantly higher in the period from 2008-9 onwards, even controlling for risk factors, which is indicative of constraints to the supply of credit.…”
Section: Surveys Of Businessesmentioning
confidence: 99%
“…One of frequently discussed topics by many authors is SMEs' credit risk in relation to their need for external financing via bank loans (Armstrong et al, 2013;Beck, 2013;Belas et al, 2014;Dobeš et al, 2017;Kozubikova et al, 2015Kozubikova et al, , 2017Kljucnikov et al, 2016;Yasnolob, & Radionova, 2017;and other authors).…”
Section: Introductionmentioning
confidence: 99%